Patriarchal Culture and the Meaning of Male Social Privilege According to ALB (Aliansi Laki-Laki Baru) - Al-Walid, Kholid; Rahman, Fadhlu (PALASTREN: Jurnal Studi Gender, 2024)
This research examines the meanings of privilege according to ALB’s perspective in three main formulations, including: first, what is the objective meaning of ALB group members towards male social privilege? Secondly, what factors encourage the emergence of this objective meaning in male privilege? Then thirdly, what are the implications of the objective meaning of male privilege for gender equality? The data collection method used in this research was personal interviews with six informants and a literature review on themes related to social privilege and the position and role of males in social reality. The data analysis used is Huberman's approaches, there are data reduction, data visualization, data verification, and data interpretation analyzed by the Manheim social method. This research concludes that male does not always protect their social privileges. ALB in this research also shows meanings that are at odds with the general view of male social privilege. Factors that influence this meaning include social factors that tend to experience and see directly the phenomenon of gender discrimination, adequate education in exploring gender issues, and a culture that tends to be patriarchal. while the implications produced by this meaning refer to various strengthening dimensions, including the intellectual and social dimension